MuICE: Mutual Influence and Citation Exclusivity Author Rank. Issue 3 (May 2016) - Amjad, Tehmina; Daud, Ali; Che, Dunren; Akram, Atia
Highlights: A mutual influence and exclusive citations based method for author ranking is proposed. It considers effect of publications, citations, and publications as first author for authors and co-authors. It also considers exclusivity in citations received by an author. Abstract: With constant growth in size of analyzable data, ranking of academic entities is becoming an attention grabbing task. For ranking of authors, this study considers the author's own contribution, as well as the impact of mutual influence of the co-authors, along with exclusivity in their received citations. The ranking of researchers is influenced by the ranking of their co-authors, more so if co-authors are seniors. Tracking the citations received by an author is also an important factor to measure standing of an author. This study proposes Mutual Influence and Citation Exclusivity Author Rank (MuICE) algorithm. We performed a sequence of experiments to calculate the MuICE Rank. First, we calculated Mutual Influence (MuInf) considering three different factors: the number of papers, the number of citations and the author's appearance as first author. Secondly, we computed MuICE incorporating all three factors of MuInf along with the exclusivity in citations received by an author. Empirically, it is shown that the proposed methods generate substantial results.